Underinvestment in agricultural research - Beintema, Nienke M. (International Food Policy Research Institute, 2020)
This year marks the 20th anniversary of the inception of ASTI. During this time, governments, donors, and international organizations have used ASTI’s evidence to guide agricultural research investment and policy decisions, to assess areas of underinvestment, to identify capacity gaps and training needs, and to demonstrate the returns to agricultural research investment. This series of notes marks this important milestone by focusing on—and updating—some of the key advancements and insights ASTI data have enabled in the past 20 years. This note focuses on the prevalence of underinvestment in agricultural research among developing countries, especially those with small- to medium-size research systems.